Анализ несущих конструкций 19-дюймовой и метрической систем для электронных средств - Ефименко, А.А.; Карлангач, А.П. (Технология и конструирование в электронной аппаратуре, 2015)
Проведено исследование и анализ различных показателей качества несущих конструкций двух конструкционных систем для определения их характеристик и сравнения между собой, а также прогнозирования перспектив их дальнейшего использования. Проведено дослідження і аналіз різних показників якості несучих конструкцій двох конструкційних систем для визначення їх характеристик та порівняння між собою, а також прогнозування перспектив їх подальшого використання. The paper deals with the research and analysis of various quality indicators of the standard mechanical structures of two constructional systems in order to define and compare their characteristics, and to predict prospects for their use. To compare these two systems we have selected parameters which make it possible to make a quantitative assessment and can be calculated on the basis of the data from standards for such mechanical structures. Research has shown that, according to considered indicators, neither 19-inch system, nor the metric system has the absolute advantage. And only in the density ratio of contacts of output electrical connectors, the metric system has real advantages. Although, it should be noted, that certain measures are taken by the developers to improve the 19-inch constructional system. This may, to some extent, explain the fact that the 19-inch system is more widely used than the metric one, and continues to evolve and develop.